PENGARUH PUPUK KASCING DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SEMANGKA (Citrullus lanatus Schard) - Hutasoit, Preddi Gunawan Monontong; Yetti, Husna; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of combination of vermicompost and dosage of NPK fertilizer to growth and production of watermelon plants and to get the best treatment. This research conducted in Experimental Garden of Faculty of Agriculture, University of Riau, August to October 2017. This research was conducted experimentally using Randomized Complete Design consists of two factors. Factor 1 is vermicompost, consisting of K0: no vermicompost, K1: 4 t.ha-1, K2: 5 t.ha-1 and K3: 6 t.ha-1. Factor 2 is NPK fertilizer, consisting of N1: 87,5 kg.ha-1, N2: 175 kg.ha-1 and N3: 262,5 kg.ha-1. Data obtained were analyzed statistically and continued with Duncan multiple-range test at 5% level. The parameters observed were number of leaf, plant length, stem diameter, flowering age, fruit diameter, fruit weight and sugar content. The results showed that in general the combination without the application of vermicompost and NPK 87.5 kg.ha-1 has supported the growth and production of watermelon plants.Keywords: Watermelon, vermicompost, NPK fertilizer.